The Influence of E-WOM, Perceived Self-Efficacy, and Herding Behavior on Online Purchase Intentions During Shopee Live Streaming of Fashion Products in Denpasar City - I Wayan Deni ARMIKA; Nengah GANAWATI; Ni Ketut SARIANI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Online purchase intention for a product is determined by several indicators.